Proteomics of Wound Exudate in Snake Venom-Induced Pathology: Search for Biomarkers To Assess Tissue Damage and Therapeutic Success - Rucavado Romero, Alexandra (2011)
Tissue damage analysis by traditional laboratory techniques is problematic. Proteomic analysis of exudates collected from affected tissue constitutes a powerful approach to assess tissue alterations, since biomarkers associated with pathologies can be identified in very low concentrations. In this study we proteomically explore the pathological effects induced by the venom of the viperid snake Bothrops asper in the gastrocnemius muscle of mice. Predominant proteins identified in the exudates included intracellular proteins, plasma proteins, extracellular matrix proteins and cell membrane-associated proteins. The presence of such proteins indicates cytotoxicity, plasma exudation, extracellular matrix degradation and shedding of membrane proteins. Some of these proteins may represent useful biomarkers for myonecrosis and microvascular damage. The effect of fucoidan, an inhibitor of myotoxic phospholipases A2, and batimastat, an inhibitor of metalloproteinases, on the pathological effects induced by B. asper venom were also investigated. Fucoidan reduced the presence of intracellular proteins in exudates, whereas batimastat reduced the amount of relevant extracellular matrix proteins. The combination of these inhibitors resulted in the abrogation of the most relevant pathological effects of this venom. Thus, proteomic analysis of exudates represents a valuable approach to assess the characteristics of tissue damage in pathological models and the success of therapeutic interventions.